Teknik Relaksasi Nafas Dalam terhadap Peningkatan Saturasi Oksigen pada Pasien PPOK - Ni Made Dwi Yunica Astriani; Aditha Angga Pratama; Putu Wahyu Sri Juniantari Sandy (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of deep breathing relaxation techniques on oxygen saturation in COPD patients. The research design used a pre-experimental one-group pre-post test design. The results showed that the average oxygen saturation value before being given deep breath relaxation was 90.19, and the average oxygen saturation after being given deep breath relaxation was 93.27. Based on the results of the paired t-test showed that the results of pre and post (0.000) < (0.05). In conclusion, there is an effect of deep breathing relaxation techniques on increasing oxygen saturation in COPD patients. Keywords: COPD, Oxygen Saturation, Deep Breathing Relaxation Technique